Excellent oxidation activity of toluene over core–shell structure Mn2O3@MnO2: role of surface lattice oxygen and Mn species. Issue 5 (14th December 2021) - Zhang, Cheng; Li, Mingyang; Wang, Xiaotong; Fan, Liman; Dong, Yongli; Zhu, Yujun
Abstract: BACKGROUND: Core–shell structure Mn2 O3 @MnO2 (MnOx ) has been prepared using KMnO4 modifying spherical Mn2 O3 assembled by nanoparticles, and applied for catalytic toluene oxidation. RESULTS: The MnOx sample calcined at 350 °C (MnOx ‐1) exhibited much higher catalytic activity compared with Mn2 O3 and MnOx ‐2 (calcined at 450 °C), good activity stability with recyclability. Bulk structure, redox ability and surface properties were characterized using various techniques. The relationship between the catalytic activity and the surface Mn and oxygen species of these catalysts is discussed in terms of these characterizations. Especially, in situ diffuse reflectance infrared Fourier transform spectroscopic measurements were used to analyze in detail the role of the surface lattice oxygen in the enhanced catalytic performance of MnOx ‐1. CONCLUSIONS: The excellent activity of the MnOx ‐1 catalyst can be attributed to the more surface Mn 4+ and many surface lattice oxygen species derived from the special core–shell structure, improving the oxidation of toluene. © 2021 Society of Chemical Industry (SCI).